Child Marriage in Malaysia: Reforming Law through the Siyasa al-Shar’iyya Framework - Abdol Malek, Muhammad Al-Ghazalli; Samuri, Mohd Al Adib; Alias, Muhammad Nazir (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
The international community sees child marriage as a traditional practice affecting children’s rights, self-development, and future. Academic literature worldwide records that child marriage harms children’s rights to health, education, and growth. Muslim scholars must engage with Islamic law frameworks to advance children’s rights in Muslim countries. Thus, Islamic law frameworks such as Siyasa al-Shar’iyya have the potential to end child marriage. Therefore, this article discusses classical and contemporary views on child marriage and focuses on Siyasa al-Shar’iyya as a framework to curb child marriage practices. This study uses a qualitative approach by applying the content analysis method to classic and contemporary Islamic legal texts. The study concluded that government could introduce legal reforms based on the framework of Siyasa al-Shar’iyya to curb child marriage. Several studies have shown that child marriage negatively impacts children’s rights and well-being. Accordingly, this could be classified as mafsada, which the authorities should avoid protecting the children’s interests. Siyasa al-Shar’iyya allows the government to prohibit any permissible act, such as child marriage, to protect the public interest. Children’s rights groups can cite such arguments to advocate against child marriage in Muslim countries.